2020
DOI: 10.5946/ce.2019.124
|View full text |Cite
|
Sign up to set email alerts
|

Endocuff-Assisted versus Cap-Assisted Colonoscopy Performed by Trainees: A Retrospective Study

Abstract: Background/Aims: The adenoma detection rate (ADR) of screening colonoscopies performed by trainees is often lower than that of colonoscopies performed by experts. The efficacy of cap-assisted colonoscopy (CAC) in adenoma detection is well documented, especially that of CACs performed by trainees. Endocuff, a new endoscopic cap, is reportedly useful for adenoma detection; however, no trials have compared the efficacy of Endocuff-assisted colonoscopy (EAC) and CAC conducted by trainees. Therefore, the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This finding supports the evidence of a higher detection with endocuff for smaller lesions, which are more likely to be missed in particular by non-expert endoscopists, and a greater overall number of polyps diagnosed as compared to capassisted colonoscopy. This aspect suggests a higher anticipated magnitude of benefit particularly for low-performing endoscopists (lower baseline ADR), as suggested by recent retrospective reports [25], whereas the improvement might be only marginal in expert operators. Third, the procedural characteristics do not seem to be influenced by the use of a specific add-on device over the other as both cecal intubation rate and insertion time were comparable in the two groups.…”
Section: Discussionmentioning
confidence: 66%
“…This finding supports the evidence of a higher detection with endocuff for smaller lesions, which are more likely to be missed in particular by non-expert endoscopists, and a greater overall number of polyps diagnosed as compared to capassisted colonoscopy. This aspect suggests a higher anticipated magnitude of benefit particularly for low-performing endoscopists (lower baseline ADR), as suggested by recent retrospective reports [25], whereas the improvement might be only marginal in expert operators. Third, the procedural characteristics do not seem to be influenced by the use of a specific add-on device over the other as both cecal intubation rate and insertion time were comparable in the two groups.…”
Section: Discussionmentioning
confidence: 66%
“…Those comparing EAC with standard colonoscopy have shown a more consistent improvement in ADR than those of CAC. A recent published retrospective study also suggested that EAC exhibited increased ADR compared with CAC when performed by trainees 29 . In our meta‐analysis, only one study included trainees, which may reduce the ADR difference between the two groups.…”
Section: Discussionmentioning
confidence: 92%
“…A recent published retrospective study also suggested that EAC exhibited increased ADR compared with CAC when performed by trainees. 29 In our meta-analysis, only one study included trainees, which may reduce the ADR difference between the two groups. Therefore, further evidence and more clinical trials are still need to compare ADR between EAC and CAC.…”
Section: Discussionmentioning
confidence: 99%
“…1, Supplemental Digital Content 1, http://links.lww.com/JCG/A818). Overall, these 57 multiarm trials testing assist devices included 31,051 patients 10–67…”
Section: Resultsmentioning
confidence: 99%